THE IMPACT OF HONEY ON CHANGE IN NUTRITIONAL STATUS IN CHILDREN WITH POOR NUTRITION - Harmiyati Harmiyati; Ariawan Soejoenoes; Sri Wahyuni M; Kun Aristiati; Soeharyo Hadisaputro (Belitung Raya Foundation, Indonesia, 2017)
Background: Toddlers are vulnerable groups to malnutrition. Thus, to maintain their nutritional status is needed. Honey is considered having health benefits that may increase the nutritional status in children. However, little is known about the impact of honey on nutritional change in Sumbawa, Indonesia. Objectives: The aim of this study is to analyze the effect of honey on changes in nutritional status in children with poor nutrition in the area of the Health Center of Lopok, Sumbawa, Indonesia Methods: This study employed a quasi-experiment design with pretest-posttest with control group. The total sample in this study were 60 children recruited by simple random sampling, divided into 2 groups, namely 30 children in an intervention group and 30 children in a control group. The sampling technique used a simple random sampling. Data were analyzed using Mann Whitney and linear regression test. Results: Findings showed that there were significant mean differences between the intervention and control group in term of weight (intervention 1.316; control 0.903), height (intervention 1.586; control 1.030), weight-for-height (W/H) z-score (intervention 0.713; control 0.595), weight-for-age (W/A) z-score (intervention 0.717; control 0.531), and height-for-age (H/A) z-score (intervention 0.847; control 0.423) with p-value < 0.05. Conclusion: There was a significant effect of honey on changes in nutritional status in children with poor nutrition. It is suggested that health providers may use honey to take care of children under nutrition to increase their appetite and change their nutritional status.